1998
DOI: 10.1126/science.280.5364.737
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Splicing Regulated by a CUG-Binding Protein in Myotonic Dystrophy

Abstract: Myotonic dystrophy (DM) is caused by a CTG expansion in the 3' untranslated region of the DM gene. One model of DM pathogenesis suggests that RNAs from the expanded allele create a gain-of-function mutation by the inappropriate binding of proteins to the CUG repeats. Data presented here indicate that the conserved heterogeneous nuclear ribonucleoprotein, CUG-binding protein (CUG-BP), may mediate the trans-dominant effect of the RNA. CUG-BP was found to bind to the human cardiac troponin T (cTNT) pre-messenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
745
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 748 publications
(771 citation statements)
references
References 18 publications
22
745
1
3
Order By: Relevance
“…We suggest two possible explanations for a low FcRn affinity for IgG based on the current notion that patients with DM manifest a generalized defect in pre-mRNA processing [37][38][39]. Perhaps the FcRn α-chain itself is abnormally spliced in a subtle but critical fashion such that the IgG binding site is distorted while the albumin binding site is preserved.…”
Section: Pathophysiology Of Dm a Second Putatively Fcrn-related Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…We suggest two possible explanations for a low FcRn affinity for IgG based on the current notion that patients with DM manifest a generalized defect in pre-mRNA processing [37][38][39]. Perhaps the FcRn α-chain itself is abnormally spliced in a subtle but critical fashion such that the IgG binding site is distorted while the albumin binding site is preserved.…”
Section: Pathophysiology Of Dm a Second Putatively Fcrn-related Diseasementioning
confidence: 93%
“…DM is a genetic disease manifesting what appears to be a generalized defect in pre-mRNA processing [37][38][39]. Its phenotype is different from FHH.…”
Section: Pathophysiology Of Dm a Second Putatively Fcrn-related Diseasementioning
confidence: 99%
“…[2][3][4] At the molecular levels, the DM1 phenotype is most likely caused by a complex molecular pathogenesis, including deficiency of myotonic dystrophy myotonin kinase (DMPK) protein, [5][6][7] haplo-insufficiency of a neighboring homeobox gene (particular the DM locus-associated homeodomain protein (DMAHP/Six 5 gene) 8 and the WD-repeat gene (DMWD) 9 and a trans-dominant misregulation of RNA homeostasis. [10][11][12][13][14][15][16] Recent experiments from transgenic mice, expressing an untranslated expanded CUG repeat under the control of the human skeletal actin promoter, showed that expanded CUG repeats are sufficient to generate DM1 muscle phenotype. 17 These data suggest that misregulation of RNA homeostasis may play a major role in DM1 muscle pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…12 In DM muscle, a downregulation of MBNL1 function and an upregulation of CELF1 function was shown. [15][16][17][18] For CELF1, multiple functions in RNA metabolism have been reported including regulation of alternative splicing, RNA stability and translational regulation of its RNA targets. [19][20][21] CELF1 interacts with the DMPK transcript, in particular with the (CUG) n repeat.…”
Section: Introductionmentioning
confidence: 99%